DIRETRIZES POLÍTICAS, EMPREENDIMENTOS PRIVADOS:A atuação da Companhia de Viação São Paulo –Mato Grosso(1908-1943) - Corrêa, Lucas Mariani (Outros Tempos: Pesquisa em Foco - História, 2012)
Our paper aims to reflect about the relationship between political guidelines of a private company targeted and inserted into the context of national security, or rather, into the constitution of the National State. In addition, we observe the performance of the Companhia de Viação São Paulo – Mato Grosso filling gaps and taking advantage of political guidelines that sought the modernization and progress of the country at all costs. The occupation and colonization of so-called "backlands", "west" or Brazilian "hollow" spaces are the axis of these guidelines. Among these "hollow" spaces, the Companhia de Viação São Paulo – Mato Grosso operated on the west end of the state of São Paulo and on the south of the former state of Mato Grosso developing sailing activities and colonization. Therefore, our focus ranges from the formation of the company in 1908 until 1943, when the sailing activity is turned into a federal agency, tracing the history of those places.